Studies of esterification using Carica papaya lipase - Neshabran , Ramachandran (2012)
In search for newer esterification method in industry, application of carica papaya lipase (CPL) satisfies that need. CPL is an enzyme that catalyses the esterification and hydrolysis. Thus it is classified as biocatalyst. This lipase is found in the unripe papaya fruit latex. The aim of this study is to study the lipolytic activity by using carica papaya lipase. To study this lipolytic activity of CPL, the latex from the unripe papaya fruit is obtained by making longitudinal incision on the fruit and collecting the latex in a beaker then dried to form latex powder. Then a series of four different alcohols and four different carboxylic acids, both ranging from three carbons to six carbons are used to in the esterification reaction. To analyze the esters formed gas chromatography (GCFID) is used. GC can be used to perform both qualitative analysis to identify the ester formed and quantitative analysis to determine the yield. Esterification using different alcohols and different carboxylic acids will hopefully show different efficiency depending on chain length. The results show that CPL can conduct lipolytic activity (esterification) with various alcohols and various carboxylic acids in industry.